A case report of nodal CD4-positive T-cell lymphoproliferative disorder with an indolent course. Issue 10 (March 2018) - Ge, Xiaowen; Zhu, Na; Yao, Jiamei; Zeng, Haiying; Su, Jieakesu; Jiang, Zhengzeng; Ji, Yuan; Tan, Yunshan; Hou, Yingyong
Abstract: Rationale: Primary nodal CD4-positive T-cell lymophoproliferative disorder with a relatively indolent process is a rare kind of lymphoproliferative disease. Here we report the first case of a 49 year-old man developed indolent nodal CD4-positive T-cell lymophoproliferative disorder. To our knowledge, based on a careful search of PubMed, it is the first case of primary nodal CD4-positive T-cell lymophoproliferative disorder. Patient concerns: A 49-year-old Chinese man presented to our hospital with fever, enlargement of multiple superficial lymphonodes more than 14 years and splenomegaly. Clinical and pathological data were collected under treatment. This case was diagnosed based on histologically characteristic, immunohistochemical staining, and lymphoid clonality testing. On immunohistochemical staining, the abnormal T-cells were CD4 positive and CD8 negative. The lymphoid clonality testing showed positive results. The patient also has enlarged spleen. Diagnoses: The patient was diagnosed with nodal CD4-positive T-cell lymophoproliferative disorder. Interventions: A watch-and-wait stratagem was performed without any chemotherapy or radiation therapy. Outcomes: During 17 years of follow-up, this case presented an indolent course without evidence of systemic dissemination. Lessons: This report presents the first case of indolent nodal CD4-positive T-cell lymophoproliferative disorder. In this case, the proliferated T-cell in the paracortex of lymph node showed T-cell receptor gene rearrangement, which indicated a clonal proliferation. There are several kinds of nodal CD4-positive T-cell lymphoma, which have a relatively aggressive course; however, this case has a relatively indolent course.